Topographies of tolerance and intolerance : responses to religious pluralism in Reformation Europe - Plummer, Marjorie Elizabeth; Christman, Victoria (Studies in Central European histories, 2018)
"Topographies of Tolerance and Intolerance challenges the narrative of a simple progression of tolerance and the establishment of confessional identity during the early modern period. These essays explore the lived experiences of religious plurality, providing insights into the developments and drawbacks of religious coexistence in this turbulent period. The essays examine three main groups of actors--the laity, parish clergy, and unacknowledged religious minorities--in pre- and post-Westphalian Europe. Throughout this period, the laity navigated their own often-fluid religious beliefs, the expectations of conformity held by their religious and political leaders, and the complex realities of life that involved interactions with coreligious and non-co-religious family, neighbors, and business associates on a daily basis"--